Comportamentos de saúde da população brasileira: situação do domicílio e diferenças geracionais - Danielle Vasconcellos de Paula Costa (2020)
Background: The relationship between sociodemographic factors and health inequalities is a relevant topic for the analysis of health behaviors. Knowing this relationship is an important contribution to the adequate coping with chronic diseases. In this sense, this study aimed to analyze the health behaviors of the Brazilian population, based on data from the National Health Survey (2013), according to the situation of the home and the different generations. Methods: This is a cross-sectional study using secondary data from the National Health Survey (2013). The PNS used a simple random sample by conglomerates, with representativeness for Brazil, its macro-regions, urban and rural population, and capitals. The prevalence of healthy eating indicators (recommended consumption of fruits and vegetables, regular consumption of fish and beans) and unhealthy (regular consumption of soft drinks and artificial juice, sweets, excess fat meats, replacement of meals with snacks) in the Brazilian population according to household situation - urban and rural. Prevalences (%) were estimated and logistic regression models were adjusted to estimate odds ratios (OR and confidence intervals (95% CI). Differences in the health behaviors of the Brazilian population, related to food consumption, alcohol abuse, smoking and physical activity during leisure and according to the different generations (traditionalists, baby-boomers, generation X, generation Y and generation Z). Prevalence (%) was estimated and Poisson regression was performed for to estimate Prevalence Ratio (PR) and confidence intervals (95% CI). Results: Regarding the food indicators according to the situation at home, higher regular consumption of beans was observed in rural areas (OR = 1.20 ; 95% CI: 1.14-1.26) and meat with excess fat (OR = 1.48; 95% CI: 1.42-1.55); and lower consumption of soft drinks (OR = 0.55; 95% CI: 0.52-0.59) and replacement of meals with snacks (OR = 0.59; 95% CI %: 0.51-0.66) On the other hand, the recommended consumption of fruits and vegetables was lower (OR = 0.89; 95% CI: 0.85-0.96) and regular fish (OR = 0.88; 95% CI: 0.84-0.92). Regarding the health behaviors analyzed according to the generations, it was observed that the generations with older representatives, the Traditionalists and Baby-boomers showed better health behaviors related to food, with a higher prevalence of consumption of fruits and vegetables and less of soft drinks and artificial juices, in addition to lower prevalence of alcohol abuse. On the other hand, the younger generations - Generations Y and Z, compared to Traditionalists, had a higher prevalence of the habit of not smoking and were more active at leisure. Conclusion: Differences were observed in the food consumption of Brazilians living in rural and urban areas, as well as in health behaviors across different generations. Brazilians living in rural areas reported a greater chance of maintaining a traditional dietary pattern, with the consumption of minimally processed foods, especially beans; and lower consumption of ultra-processed foods; despite the lower consumption of fruits and vegetables, and fish. The differences identified according to the situation of the home and the different generations investigated denote the importance of promoting health promotion policies that respect and value traditions, and consider cultural differences, valuing their positive aspects and reinforcing the need to align with the objectives of health.